2013
DOI: 10.1371/journal.pgen.1003713
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor independent-1 Maintains Notch1-Dependent Transcriptional Programming of Lymphoid Precursors

Abstract: Growth factor independent 1 (Gfi1) is a transcriptional repressor originally identified as a gene activated in T-cell leukemias induced by Moloney-murine-leukemia virus infection. Notch1 is a transmembrane receptor that is frequently mutated in human T-cell acute lymphoblastic leukemia (T-ALL). Gfi1 is an important factor in the initiation and maintenance of lymphoid leukemias and its deficiency significantly impedes Notch dependent initiation of T-ALL in animal models. Here, we show that immature hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 75 publications
(108 reference statements)
0
15
0
Order By: Relevance
“…[52][53][54] Similar analyses with murine Gfi1b-deficient HSCs, megakaryocytes, or erythroid cells demonstrated that Gfi1b helps to establish gene expression programs necessary for the development of both erythroid and megakaryocytic lineages 29,32,55 and confirms the complementary roles of Gfi1 and Gfi1b in hematopoiesis already suspected by their differential, cell type-specific expression pattern.…”
Section: 3944-48mentioning
confidence: 67%
“…[52][53][54] Similar analyses with murine Gfi1b-deficient HSCs, megakaryocytes, or erythroid cells demonstrated that Gfi1b helps to establish gene expression programs necessary for the development of both erythroid and megakaryocytic lineages 29,32,55 and confirms the complementary roles of Gfi1 and Gfi1b in hematopoiesis already suspected by their differential, cell type-specific expression pattern.…”
Section: 3944-48mentioning
confidence: 67%
“…Similarly, although the basic helix–loop–helix (bHLH) factor Lyl1 plays its best-known role in hematopoietic progenitors and B-cells 56, 57 , deletion of Lyl1 severely impairs development of lymphoid precursors in bone marrow and specifically reduces ETP expansion, progression to DN2, and early T-cell survival 56, 58, 59 . Lyl1, working in dimers with E2A or HEB, probably helps to maintain expression of the crucial ETP–DN2 growth factor receptor Kit, similar to the function of the related protein SCL ( Tal1 ), and promotes expression of Gfi1 , a regulatory factor required for normal generation of ETPs and for proper responses to Notch signaling 58, 60, 61 . Erg and Hhex are implicated in early T-cell self-renewal in both normal and malignant contexts 62, 63 .…”
Section: Critical Transcription Factors In the Induction And Establismentioning
confidence: 99%
“…Recently, Gfi1 has been shown to be essential in LMPPs and ETPs to enable cells to be stimulated by Notch signals. Without Gfi1, Notch signaling is toxic, and the cells fail to activate a T-cell gene expression program (Phelan et al , 2013). The mechanism is still being dissected.…”
Section: Dynamic Transcription Factor Expressionmentioning
confidence: 99%